Extracorporeal Membrane Oxygenation in Complex Tracheobronchial Surgery: A Series Case Reports and Systematic Review - Shu, Chen; Bao, Peilong; Ni, Yunfeng; Lei, Jie; Yan, Xiaolong; Xie, Nianlin; Zhao, Jinbo (Zhongguo fei ai za zhi, 2024)
Airway management in complex tracheobronchial surgery (TBS) remains a challenge in thoracic surgery. The use of extracorporeal membrane pulmonary oxygenation (ECMO) in thoracic surgery is rather rare, except for lung transplantation. To report the safety and efficacy of ECMO in complex TBS, a total of 5 patients with tracheobronchial and bronchial reconstructive surgery supported by ECMO in the Department of Thoracic Surgery of Tangdu Hospital, Air Force Medical University from May 2019 to June 2024 were collected. Among them, 4 cases of tracheal tumor (including long-segment trachea resection and reconstruction, or carinal resection and reconstruction) and 1 case of acute airway obstruction caused by tracheal rupture were included, all of which were performed in veno-venous ECMO (V-V ECMO) mode. Systemic heparinization was used in 2 patients, and anticoagulation was not performed in 3 patients, which were maintained only by ECMO heparin-coated lines. 4 patients recovered well after surgery, and 1 patient die